Some Signal Propagation and Traffic Handover Aspects of a Mobile Radio Network for High-Speed Railways - Lipovac, Vlado; Sertić, Antun; Milković, Mateo (Promet - Traffic&Transportation, 2012)
Taking advantage of GSM's elaborated mobility managementand its intemational roaming capability, the IntemationalUnion of European Railroad Operators (UJC) has decidedto build a supra-national rail radio network based on enhancedGSM technology.In this pape1; some implemmtation aspects specific to railroadradio environment resulting from the effects of vehiclespeed - in particular Doppler shift - are discussed, and an'off-line' algorithm for the traffic handover is proposed, whichoffers bel/er radio link reliability and less critical timing constraintsthan conventional handover schemes. More reliablehandover is of vital significance in the case of high-speed trainssince the radio link is supposed to cany the automatic controlsignals (ATC), too.